The role of β-catenin in cardiac diseases - Ni, Beibei; Sun, Meijuan; Zhao, Jun; Wang, Jiao; Cao, Zhanqi (Frontiers in Pharmacology, 2023)
The Wnt/β-catenin signaling pathway is a classical Wnt pathway that regulates the stability and nuclear localization of β-catenin and plays an important role in adult heart development and cardiac tissue homeostasis. In recent years, an increasing number of researchers have implicated the dysregulation of this signaling pathway in a variety of cardiac diseases, such as myocardial infarction, arrhythmias, arrhythmogenic cardiomyopathy, diabetic cardiomyopathies, and myocardial hypertrophy. The morbidity and mortality of cardiac diseases are increasing, which brings great challenges to clinical treatment and seriously affects patient health. Thus, understanding the biological roles of the Wnt/β-catenin pathway in these diseases may be essential for cardiac disease treatment and diagnosis to improve patient quality of life. In this review, we summarize current research on the roles of β-catenin in human cardiac diseases and potential inhibitors of β-catenin, which may provide new strategies for cardiac disease therapies.